Assessment of prevalence of hypertension and its risk factors among adult tribal population residing in Lohandiguda block of bastar district of Chhattisgarh - Nisha Meshram; Nirmal Verma; Neha Shrivastava; Manish A Prasad; Kamlesh Jain; Swapnil V Shinkar (Wolters Kluwer Medknow Publications, 2023)
Background: Hypertension is known as the silent killer. It comprehends the top rank in non-infectious disease amongst adults; accountable for the deaths every year across the world. It is essential to consider the individual impact of risk factors and their impact on hypertension. This study thus elicited the socio-demographic characteristics, the prevalence of hypertension and associated risk factors, and its impact on adults with hypertension. To estimate the hypertension prevalence and its associated risk factors among adult tribal populations aged 25-60 years residing in Lohandiguda block of Bastar district of Chhattisgarh. Material and Methods: A community-based cross-sectional analytical study was used and the setting was done at the field practice area under the three primary health centers of Lohandiguda block, Bastar district of Chhattisgarh. It was carried out among 330 adult tribes residing for ≥1 year in the present locality. Data was collected by door-to-door visits through pre-designed, pretested, semi-structured questionnaire via face-to-face interview method and anthropometric measurement was done by using standard guidelines. The sampling method was multistage sampling. IBM SPSS STATISTICS-20.0 (IBM Corp., Armonk, NY, USA) software. Results: The overall prevalence of pre-hypertension and hypertension among tribal subjects was 34.9% and 47.3%, respectively. Of total hypertensive 27.3% were having stage-1 hypertension, 13.9% were having stage-2 hypertension and 6.0% were already diagnosed cases. Risk factors found in multivariate analysis are occupation (unemployed 0.012), frequency of smokeless tobacco used per day (0.,017) and central obesity (0.000). Conclusions: As hypertension is a multi-factorial disease the study found strong predictors like occupation, frequency of smokeless tobacco per day and having central obesity with significant difference.